Implementation of a Web Platform for the Preservation of American Native Languages - Melgarejo, N.; Camacho, L. (Institute of Electrical and Electronics Engineers, 2018)
In the 1940 Peruvian Population Census was found that 7 million Peruvians spoke Quechua, at that time two out of every three Peruvians used the Quechua language. According to the 2007 census only 3.3 million Peruvians spoke Quechua, that means just one in nine Peruvians can speak the Quechua language nowadays. This figures show that there is a tendency to decrease over the years with high risk of extinction. The main objective of this research is the creation of a corpus repository linked to a web platform (https://siminchikkunarayku.pe) to contribute to preservation of the Peruvian native languages.
Keywords: Census; Population; Extinction (optical mineralogy); Computer science; Native american; World Wide Web; Ethnology; Geography; History; Sociology; Demography; Biology; https://purl.org/pe-repo/ocde/ford#5.04.02